EVALUATION OF THE PHYSICO-MECHANICAL PROPERTIES OF PLYWOOD PANELS AND LAMINATED VENEER LUMBER OF Pinus glabra Walt. - Bilik, Annah Carolina Bajaluk; Trianoski, Rosilani (Floresta, 2022)
This work evaluated the potential of the species Pinus glabra for the production of laminated panels, as well as the effect of the density of the veneers and their combination on the quality of the product. The plywood and laminated veneer lumber were produced from two veneer density classes and the combination between them, namely: panels with veneers from 0.33 to 0.40 g/cm3; panels with veneers ranging from 0.41 to 0.48 g/cm3; and panels with veneers of 0.33-0.40 g/cm3 in the inner layer and 0.41-0.48 g/cm3 in the outer layer, resulting in 6 treatments. Phenol-formaldehyde was used as adhesive, whose formulation was 100 pbw of adhesive, 20 pbw of extender, 10 pbw of filler and 20 pbw of water, and applied at a grammage of 180 g/m². The pressing parameters were 1 MPa and temperature of 160ºC for 8 minutes. The evaluation of the quality of the panels was performed through tests of apparent specific gravity, static bending and glue line shear strength, according to European standards. The results presented that the production of panels, from the classification of veneers by densities and combination between them, provides gains in strength and stiffness. The parallel direction of the veneers (in LVL) provided gains in strength and stiffness when compared to panels produced with veneers perpendicular to each other (plywood), being, therefore, the most suitable for structural use. Finally, we have the conclusion that the species Pinus glabra has potential for producing laminated panels.